(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Peptide therapeutics are an accelerating class of biologics valued for their exceptional specificity, potency, and safety. By mimicking natural hormones or enzymes, these short amino acid chains offer highly targeted interventions. Yet, clinical success hinges on strict quality control, requiring exceptional purity, stability, solubility, and contaminant management under global regulatory standards (FDA/EMA) and Good Manufacturing Practices (GMP). Recent engineering breakthroughs have revolutionized this landscape. Novel delivery systems, such as nanoparticle encapsulation and sustained-release formulations, directly overcome traditional barriers of poor stability and bioavailability. Furthermore, tailoring peptides to distinct disease biomarkers paves the way for highly individualized precision medicine. With robust ongoing research across oncology, metabolic disorders, and infectious diseases, peptide-based platforms are poised to deliver the next generation of targeted clinical therapies